Subvalvular techniques enhanced with endoscopic robotic mitral valve repairCentral MessagePerspective - Michael Dorsey, MD; Les James, MD, MPH; Shashwat Shrivastava, MD; Didier Loulmet, MD; Eugene A. Grossi, MD (JTCVS Techniques)
Objective: Totally endoscopic intracardiac robotic surgery is generally limited to uncomplicated mitral valve surgery. With experience, our team has developed a more aggressive approach to robotic cardiac surgery that allows for repair of a broad spectrum of mitral valve pathologies. We report complex subvalvular procedural advancements associated with this approach secondary to enhanced team experience and capabilities. Methods: All robotic mitral procedures performed by a 2-surgeon team in a quaternary care medical center from July 2011 to May 2022 were reviewed. Natural language-processing techniques were used to analyze operative reports for subvalvular repair techniques. Complex subvalvular techniques included papillary muscle repositioning, division of secondary anterior leaflet chordae, septal myomectomy, division of aberrant left ventricular muscle band attachments, and left ventricular patch reconstruction. The surgical experience was divided into 2 periods: early robotic experience (pre-2018) versus late (2018 onwards). Baseline demographics, outcomes, and subvalvular techniques were analyzed and compared. Results: A total of 1287 intracardiac robotic operations were performed by a 2-surgeon team. Thirty-day mortality was 0.6% (8/1287). Mitral valve repair was performed in 1024 patients. The mean age was 61 years (range, 18-90 years), and 15% were >75 years old; 29 patients (2.8%) had previously undergone cardiac surgery. There was a significant increase with experience in the application of advanced subvalvular techniques between the early versus late period (52.3% [268/512] vs 74.2% [380/512] (P < .001)). Conclusions: An experienced 2-surgeon team can perform progressively more complex robotic subvalvular repair techniques. These subvalvular techniques are a surrogate for team proficiency and capabilities.